2009
DOI: 10.1002/hep.23121
|View full text |Cite
|
Sign up to set email alerts
|

Targeted expression of uncoupling protein 2 to mouse liver increases the susceptibility to lipopolysaccharide/galactosamine-induced acute liver injury

Abstract: Normal hepatocytes do not express endogenous uncoupling protein 2 (UCP2) in adult liver, although Kupffer cells do, and it is strikingly induced in hepatocytes in steatotic liver and obese conditions. However, the direct link of UCP2 with the pathogenic development of liver diseases and liver injury remains elusive. Here we report that targeted expression of UCP2 to mouse liver increases susceptibility to acute liver injury induced by lipopolysaccharide (LPS) and galactosamine (GalN). UCP2 appears to enhance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…Furthermore, we could previously demonstrate that UCP2 deficiency is protective in a murine model of endotoxemic acute liver failure [16]. In line with this, targeted expression of UCP2 to mouse liver is reported to increase the susceptibility to lipopolysaccharide/galactosamine-induced acute liver injury [25].…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, we could previously demonstrate that UCP2 deficiency is protective in a murine model of endotoxemic acute liver failure [16]. In line with this, targeted expression of UCP2 to mouse liver is reported to increase the susceptibility to lipopolysaccharide/galactosamine-induced acute liver injury [25].…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, overexpression of uncoupling protein-2 (UCP2) in the liver can cause acute liver injury [26]. The natural product genipin (GNP), an inhibitor of UCP2, was shown to enhance ATP production in isolated pancreatic islets and improve mitochondrial function in mice [27,28].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…15,16 Therefore, LPS/D-GalN-induced hepatitis is a wellestablished model to mimic liver injury induced by intestinal endotoxemia in a clinical setting. [17][18][19] The present study aims to examine the in vivo role of PDCD4 in LPS/D-GalN-induced liver injury using PDCD4-deficient mice and wild-type (WT) mice. We first demonstrated that PDCD4 deficiency exacerbated LPS/DGalN-induced hepatocyte apoptosis and necrosis, and enhanced liver injury in PDCD4-deficient mice was due to an increased release of inflammatory factors induced by excessive activation of the MAPK and NF-kB pathways.…”
mentioning
confidence: 99%